The interpretation of the revelatory events in John 17:24-26: An exegetical exercise - Merwe, D. J. van der (Verbum et ecclesia, 2004)
John 1:18 spells out the purpose of the incarnation of the Son of God (to make God known - ejxhgei`sqai) and functions as the transition from the prologue to the rest of the Fourth Gospel. With verse 18 the Evangelist signals that the revelation of God, through his Son, is intrinsic to the composition of the Fourth Gospel. This is particularly evident in chapter 17(:24-26), where we find an explicit reference to a triadic revelation: revelation during Jesus’ ministry, post-resurrection revelation, and future eschatological revelation. The aim of the investigation of Jn 17:24-26 is to gain an understanding of what Jesus (and the Fourth Evangelist) tries to emphasize and to communicate to his disciples (and the readers) concerning his revelatory (-salvific) mission. In the exposition of this text it is pointed out what each phase in the triadic revelation comprises, and how these phases of revelation link to one another.